IMPLEMENTASI STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PADA CONFETTI PROJECT SAMARINDA KALIMANTAN TIMUR - Esy Vita Tresia Waty (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The background of this research is to remember the importance of marketing to be able to maintain and increase product sales from Confetti Project.The purpose of this research is to find out the marketing strategies used by Confetti Project  in increasing the number of sales of these products. This research uses descriptive research methods in the form of written or oral data from interviews with industry owners.The results of this study indicate thet the implementation of the mareting mix strategy in increasing sales volume at Confetti Project Samarinda Kalimantan Timur has been going very well.